KEHIDUPAN SOSIAL EKONOMI PETANI KOPI DI KECAMATAN LEMBAH MASURAI KABUPATEN MEREANGIN PROVINSI JAMBI TAHUN 1999-2011 - Suparjo, Hardi; Husnita, Liza; Aziz, Zulkifli (Pendidikan Sejarah, 2013)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTThis thesis tells about the social-economic history with title â Social-economic of coffeeâs farmers in the District Lembah Masurai Kabupaten Merangin Provinsi Jambi (1999-2011)â. It is interesting to discuss because the presence of coffee cultivation in Kecamatan Lembah can give the impact for development of economy to be better. The research problem are: How does the emergence of the coffee crop in the district Lembah Masurai since (1999-2011), How the development of coffeeâs farmers in the district Lembah Masurai since (1999-2011), How the coffeeâs farmers influences social-economic in District Lembah Masurai since (1999-2011). Beside that the purpose of this study also discuss about social- economic life of coffeeâs farmers in District Lembah Masurai Kabupaten Merangin Provinsi Jambi since 1999-2011. This research includes historical research , this study followed the methods of history : 1 ) Heuristics , 2 ) source criticism , 3 ) interpretation , and 4 ) the presentation of the results of a research thesis . Transition from peasant agriculture cinnamon to coffee farmers, income changes, in addition, reaches the high standart in the reality of human life. Changes occur anywhere; including in District Lembah Masurai Kabupaten Merangnin Jambi Province. Lembah Masurai districts have good potential of Â agricultural. Over time, so many developments of human live in Lembah Masurai District. In 1999 the District of Okanagan Masurai more interested in planting coffee as compared to other crops. In 2001, standar live of society are more be better than before, we can see that by the education system, building system and economic system.Â